Nature of Geography and Their Relation with Pedagogical Practices in School: Enhancing Subject Knowledge in Geography Education (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Perception of subject has an amazingly pressing assignment to do because nature of empowering lays on the instructors cognizance of subject. Teachers are training, knowing and understanding the development and sequencing of thoughts, terms and making authentic data and understanding that is principal to grasp the possibility of the subject. „When there is a shortfall of ability of subject among the teachers then the idea of instructing learning association and understudies' test outcomes are at risk‟ (Smithers and Robinson, 2005). An overall made foundation of understanding of subject data is a basic crucial for show a subject, for instance, geography reasonably and successfully. Understudies can't be told just to think. They should have an interesting point, is what Lambert conveys his viewpoint on the subject (Lambert, 2009b, p.1). With respect to instructive program of geography, teachers‟ nonattendance of subject data and seeing eventually have been perceived as hazardous in the United Kingdom, Netherlands similarly as in various countries of the world. Probably that cognizance of enlightening substance data is basic for the teachers‟ for suitably executing the unprecedented thought of geography.